Evaluation of Anti-diarrheal Activity of Probiotic by Castor Oil Induced Diarrhoea in Swiss Albino Mice Model - Solanki, Himanshu K.; Shah, Dushyant A.; Patel, Chirag A.; Jani, Girish K. (Current Bioactive Compounds, 2018)
Background: Diarrheal disease is a leading cause of mortality and morbidity, especially among children in the developing countries resulting in a major health care problem. So, the present study was designed to investigate antidiarrheal activity and mechanism of action of probiotic using the Swiss mice model of castor oil induced diarrhea. Methods: In the current study, we selected the model of diarrhea induced by castor oil in the Swiss albino mice to examine the effects of preventive treatment containing single as well as multiple oral administrations of probiotic Bacillus coagulans Unique IS2 and Bifidobacterium bifidum at dose 1010 CFU/kg and to examine the mechanisms of action of probiotic by studying its co-administration with antagonist L-arginine. During an observation period, the time of onset of diarrhea, total quantity of faecal output and weight of faeces defecated by the animals were documented. Results: Probiotic Bacillus coagulans Unique IS2 and Bifidobacterium bifidum at dose 1010 cfu/kg, p.o. significantly (p < 0.05-0.001) reduced the faecal output and delayed the onset of diarrhea induced by castor oil when matched with the diarrheal control The effect of probiotic Bacillus coagulans Unique IS2 and Bifidobacterium bifidum was significantly reduced by antagonist L-arginine. Conclusion: The experimental findings suggest a unique mechanism of action for probiotic Bacillus coagulans Unique IS2 and Bifidobacterium bifidum comprising a probable inhibition of nitric oxide production by probiotic. Probiotic Bacillus coagulans Unique IS2 and Bifidobacterium bifidum possess good antidiarrhoeal use as biotherapeutic agent in the treatment of diarrhea.
Keywords: nitric oxide